Desenvolvimento de bioprocessamento consolidado utilizando levedura com secreção de enzimas hidrolíticas - Ramos, Márcio Daniel Nicodemos (2023)
Consolidated Bioprocessing (BPC) for the production of second-generation (2G) ethanol is an emerging technology in which the production of hydrolytic enzymes, enzymatic hydrolysis and fermentation of pentoses and hexoses occur in the same reactor. The recombinant yeast Saccharomyces cerevisiae AC14 stands out for producing seven hydrolytic enzymes (β-glucosidase, β-xylosidase, xylanase, endoglucanase, cellobiohydrolase I and II, and acetyl xylan esterase), with great potential for application in CBP under industrial conditions. In this sense, the objective of this dissertation was to contribute to the development of CBP from sugarcane bagasse using this high performance recombinant yeast (strain AC14), aiming at application in biorefineries. The experiments were carried out in mini-reactors equipped with a CO2 outlet, at 35 ºC and with an initial optical density of 100. The supernatants generated were analyzed in relation to enzymatic activities (total cellulases, xylanase, β-glucosidase and β xylosidase) and to the composition of substrates and products. In a first step, CBP was evaluated in synthetic medium (influence of culture conditions: substrates, pH and oxygen supply) with free cells, in simple and repeated batches, and the conditions that favored the production of enzymes were identified: medium containing corn cob xylan, carboxymethylcellulose, cellobiose, glucose and xylose and pH 5.5, reaching 2.1 IU.g 1 cell of total cellulases, 102.0 IU.g-1 cell of xylanases, 7.4 IU.g-1 cell of β-glucosidase and 25.5 IU.g-1 cell of β-xylosidase. The aerobic condition favored growth to the detriment of ethanol production, but did not alter enzyme production in relation to fermentative conditions. Repeated batches were carried out in the selected medium, reaching total conversion in the ten cycles and productivity and average yield in ethanol of 0.86 g.L-1 .h 1 and 0.4 g.g-1 . In a second stage, BPC cultivations were carried out with real industrial medium containing sugarcane bagasse pre-treated by hydrothermal and acid, also evaluating the doping with soy protein and the freezing of the pre-treated fraction as auxiliary treatments to improve enzyme access and intensify CPB. The process with sugarcane bagasse pre-treated by hydrothermal route was superior to that obtained by the acid route due to the lower concentration of inhibitors. The freezing of cellulignin favored the CBP, while the addition of soy protein had no influence on the studied conditions, obtaining 14.1 g.L-1 and 1.3 g.L-1 .h-1 of ethanol using liquor and cellulignin (10 g.L-1 ) hydrothermal. Finally, in step 3 of this work, the applicability and immobilization conditions of the yeast AC14 in calcium alginate were evaluated, varying the diameter of the microspheres, cell load and agitation. Diffusional limitations were noted in the experiments with immobilized cells, but without compromising the total consumption of the substrate. It was found that the presence of agitation favored the diffusion of enzymes into the reaction medium. Smaller diameters and higher cell loads within the microspheres improved fermentation performance, probably by creating a favorable microenvironment and decreasing diffusional limitations, yielding 11.9 g.L-1 (1.1 g.L-1 .h-1 ) of ethanol. Thus, the present study generated a broad overview of CBP, which covered fermentation conditions, real raw material and cell immobilization, contributing to expand knowledge regarding this promising technology for application in the context of obtaining 2G ethanol.